Application of Standardized Patients in Clinical Teaching of Optometry Interns: Taking Orthokeratology Lens Fitting as an Example - Yang, Xiaodi; Lyu, Yong; Wang, Weiqun (Journal of Educational Research and Policies, 2025)
As optometry develops in China, optometry clinical education is becoming increasingly important, especially in improving students' practical skills and clinical decision-making ability. This article explores the role of standardized patients (SPs) in optometry clinical teaching, taking the fitting of orthokeratology lenses as an example for in-depth discussion. SPs are professionally trained personnel who simulate real patient scenarios and provide students with a safe and controlled environment to practice clinical procedures, including refractive error assessment, corneal topography examination, and orthokeratology lens fitting and fitting assessment. Using SPs allows students to improve basic skills such as technical proficiency, communication, and diagnostic judgment without taking the risks of working with actual patients. Through case-based simulations, SPs provide real-time feedback to help students improve their operational skills and clinical decision-making ability. This approach is different from traditional methods in that it provides practical experience, cultivates independent problem-solving skills, and enhances doctor-patient communication. Ultimately, integrating SPs into optometry education can provide a comprehensive learning experience that prepares students for real-world clinical practice, improves the quality of training, and helps to cultivate highly skilled optometry interns.